Clusters of premenstrual symptoms in women with PMDD: Appearance, stability and association with impairment - Kaiser, Gudrun; Janda, Carolyn; Kleinstäuber, Maria; Weise, Cornelia (Journal of Psychosomatic Research, 2018)
Although premenstrual dysphoric disorder (PMDD) is assumed to be a homogenous diagnostic entity, it is hallmarked by highly diverse clinical symptoms. In this study, we investigate symptom clusters in women prospectively diagnosed with severe premenstrual syndrome (PMS) or PMDD using factor analysis; analyze the stability of the structures of different symptom patterns and their association with impairment at work, in recreation, and in relationships. A total of 174 prospective symptom diaries were analyzed with principal axis factoring revealing six clusters named affective dysphoria, somatic dysphoria, irritability, breast/body sensitivity, pain, and eating behavior. Cronbach's alpha was good for all clusters (0.83 to 0.91) with the exception of the cluster pain (0.69). Clusters of symptoms appeared to be stable between two consecutive menstrual cycles (except of pain and eating behavior) and between two cycles with a waiting period of eight weeks in between. Multiple regression analyses showed different associations of the clusters with impairment. Somatic dysphoria was the cluster most strongly associated with impairment. The results indicate that in severe PMS/PMDD, different symptom patterns should be considered. As the risk of impairment differs between symptom clusters, individual treatment options should be considered and further investigated in research and treatment.
CRIS-Team Scopus Importer:2024-03-27
Keywords: Premenstrual changes; Premenstrual dysphoric disorder (PMDD); Premenstrual syndrome (PMS); Prospective assessments; Symptom diary